Baseline prevalence of molecular marker of sulfadoxine/pyrimethamine resistance in Ebonyi and Osun states, Nigeria: amplicon deep sequencing of dhps-540. (21st January 2023) - Olukosi, Adeola Y; Ajibaye, Olusola; Omoniwa, Omowunmi; Oresanya, Olusola; Oluwagbemiga, Aina O; Ujuju, Chinazo; Ekholuenetale, Michael; Maxwell, Kolawole; Sutherland, Colin J; Tibenderana, James K; Beshir, Khalid B
Abstract: Background: Chemoprevention plays an important role in malaria control strategy. Perennial malaria chemoprevention (PMC) using sulfadoxine/pyrimethamine (SP) is a WHO-approved strategy to combat malaria in young children and may lead to drug pressure. Introducing SP-PMC may therefore be compromised due to the emergence of Plasmodium falciparum resistant to SP, particularly mutation at K540E of the dihydropteroate synthase ( dhps ) gene. Molecular surveillance of resistance markers can support assessment of antimalarial efficacy and effectiveness. High prevalence of 540E is associated with reduced effectiveness of SP, and areas with more than 50% prevalence are considered unsuitable for intermittent preventative treatment in pregnancy (IPTp) implementation. Assessing 540E prevalence is an important undertaking before implementation of SP-PMC. Methods: We conducted a rapid surveillance of dhps- 540E to assess the suitability of SP as PMC in field studies from Ebonyi and Osun states in Nigeria. We used an in-house developed amplicon deep-sequencing method targeting part of the dhps gene. Results: Our data reveal that 18.56% of individuals evaluated carried the 540E mutation mixed with the WT K540. Mutant variant 540E alone was not found, and 80% of isolates harboured only WT (K540). Clonal analysis of the sequencing data shows a very low proportion of 540E circulating in both states. Conclusions: Our data show that both states are suitable for SP-PMC implementation and, based on this finding, SP-PMC was implemented in Osun in 2022. Continuous monitoring of 540E will be required to ensure the chemoprevention effectiveness of SP in Nigeria.